RDPLF annual report: Profile of peritoneal dialysis patients in France in 2022, synthetic raw results - Christian Verger; Emmanuel Fabre (RDPLF, 2023)
We present the main descriptive data of patients treated by peritoneal dialysis in France in 2022 in the form of tables and graphs. Patients from DROM-TOM and other French-speaking countries and regions of the RDPLF will be described in a future issue in order to group together regions with similar socio-economic and climatic characteristics. Since the SARS-Cov2 epidemic in 2020 and the three years that followed, the number of patients treated by peritoneal dialysis in France has decreased by 6.7%, but with significant regional variations ranging from +20% to -30%. Vascular (23.5%) and diabetic (20.5%) nephropathies are the most numerous. The average age for CAPD is 70 years and 58 years for APD 36% of patients are assisted by a nurse and 5% by a family member. The average waiting time for transplant patients was 20 months. There is a great difference in the technique of catheter placement with a catheter survival of 72% at 5 years.